Modeled microgravity and hindlimb unloading sensitize osteoclast precursors to RANKL mediated osteoclastogenesis - Saxena, Ritu (2010)
Mechanical forces are essential to maintain skeletal integrity, and microgravity exposure leads to bone loss. The underlying molecular mechanisms leading to the changes in osteoblasts and osteoclast differentiation and function remain be to fully elucidated. Due to the infrequency of spaceflights and payload constraints, establishing in vitro and in vivo systems that mimic microgravity conditions becomes necessary. We have established a simulated microgravity (modeled microgravity, MMG) system to study the changes induced in osteoclast precursors. We observed that MMG, on its own was unable to induce osteoclastogenesis of osteoclast precursors, however, 24h of MMG activates osteoclastogenesis-related signaling molecules ERK, p38, PLCγ2, and NFATc1. RANKL (and/or M-CSF) stimulation for 3-4 days in gravity of cells that had been exposed to MMG for 24h, enhanced the formation of very large TRAP positive multinucleated (>30 nuclei) osteoclasts accompanied by an upregulation of osteoclast marker genes- TRAP and cathepsin K. To validate the in vitro system, we established the hindlimb unloading system using BALB/c mice and observed a decrease in BMD of femurs and a loss of 3D microstructure of both cortical and trabecular bone as determined by microCT. There was a marked stimulation of osteoclastogenesis as determined by the total number of TRAP positive multinucleated osteoclasts formed and also an increase in RANKL stimulated osteoclastogenesis from precursors removed from the tibias of mice after 28 days of hindlimb unloading. Contrary to earlier reported findings, we did not observe any histomorphometrical changes in the bone formation parameters. Thus, the above observations indicate that microgravity sensitizes osteoclast precursors for increased differentiation. The in vitro model system described here is potentially a valid system for testing drugs for preventing microgravity induced bone loss by targeting the molecular events occurring in microgravity-induced enhanced osteoclastogenesis.